2009
DOI: 10.1007/s00421-009-1118-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between electrically evoked and voluntary isometric contractions for biceps brachii muscle oxidative metabolism using near-infrared spectroscopy

Abstract: This study compared voluntary (VOL) and electrically evoked isometric contractions by muscle stimulation (EMS) for changes in biceps brachii muscle oxygenation (tissue oxygenation index, DeltaTOI) and total haemoglobin concentration (DeltatHb = oxygenated haemoglobin + deoxygenated haemoglobin) determined by near-infrared spectroscopy. Twelve men performed EMS with one arm followed 24 h later by VOL with the contralateral arm, consisting of 30 repeated (1-s contraction, 1-s relaxation) isometric contractions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
3
18
0
1
Order By: Relevance
“…Prior to each testing session, the NIRO‐200 initialization procedure was carried out to set each laser power automatically in order to establish the optimum measurement conditions, and all used procedures were previously described by [21,22]. NIRS signals were sampled at 2 Hz by the NIRO‐200 apparatus and collected simultaneously with torque data using the Biopac Acqknowledge Data Acquisition software.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to each testing session, the NIRO‐200 initialization procedure was carried out to set each laser power automatically in order to establish the optimum measurement conditions, and all used procedures were previously described by [21,22]. NIRS signals were sampled at 2 Hz by the NIRO‐200 apparatus and collected simultaneously with torque data using the Biopac Acqknowledge Data Acquisition software.…”
Section: Discussionmentioning
confidence: 99%
“…They examined the biceps brachii muscle and they used a NIRS device identical to the one used in the present study to evaluate oxygenation. They concluded that local O 2 demand during a NMES-induced isometric contraction of 30 seconds was similar in using a 30 Hz and a 75 Hz current [47,48]. …”
Section: Discussionmentioning
confidence: 99%
“…They also used near infrared spectroscopy, which is a technique particularly suitable for investigating local metabolic changes of stimulated muscles (Muthalib et al 2009), and were able to demonstrate that, besides contractile activity, muscle oxygen consumption and hyperaemia were significantly increased when motor point location was carefully determined with a pen electrode rather than being inferred from several legally marketed motor point charts. We recommend that the procedure described by Gobbo et al (2011), which is completed in less than a minute, should be consistently incorporated in both clinical and research contexts to optimize NMES application.…”
Section: Nmes Methodologymentioning
confidence: 99%